Endophyte Extract From Nattle (Urtica dioica L.) Against Staphylococcus aureus and Escherichia coli - Azim, Muhlisun; Novasari, Novasari; Hariadi, Puspawan; Febriani, Yuyun; Yuliana, Tri Puspita (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2022)
Endophytes are microorganisms that colonize the plant host tissue. Endophytic colonies are able to produce secondary metabolites in accordance with their host plants, endophytes have been found in every plant species studied to date and are recognized as a source of new natural compounds that have the potential to be exploited in medicine. This study aims to isolate and obtain endophytic fungi and to test secondary metabolites that have the potential as antibacterial against Staphylococcus aureus and Escherichia coli. Plant samples were taken around the village of Mamben, Wanasaba. The research method used is experimental laboratory. This research was conducted by isolating and identifying endophytic fungi from nettle stems. Obtained a type of endophytic fungal strain using Potato Dextrose Agar (PDA) media. The production of secondary metabolites of endophytic fungi was obtained by fermentation method using brown rice for a month then macerated for 3 days using methanol solvent and tested for secondary metabolites and antibacterial activity. The endophytic fungal extract of nettle stem contains alkaloids and flavonoids and is able to inhibit the growth of Staphylococcus aureus bacteria with the highest concentration of 60% with an inhibition zone of 18 mm. whereas, the extract of nettle stem endophytic fungus on Escherichia coli has not an inhibition zone.